Editorial - Clavijo, Amparo (Colombian Applied Linguistics Journal, 2012)
For the celebration of twenty years of our graduate program in Applied Linguistics to Teaching English as a Foreign Language in Colombia, we have prepared this special issue that contains reports of research carried out by faculty and graduate students on issues related to Discourse Analysis (DA) in Educational Contexts. Putting together an issue on this recently introduced domain of applied linguistics in our program was an interesting, yet very challenging one-year project for both writers and the editorial team. We aimed at having graduates from the program who have done research on DA during the last 4 years, prepare a manuscript to share with the local, national and international audience of the Colombian Applied Linguistics Journal. We sent out the invitation to the academic community in April 2011 and received a good number of articles. The abstracts of these submissions were evaluated by the editorial committee, initially and those that were approved were sent out for double blind peer evaluation. As a result, 11 articles were approved for publication in this issue.